Effect of Incorporation of Potato on the Quality of Restructured Spent Hen Meat Blocks - Gupta, Swati; Sharma, B.D.; Mendiratta, S.K.; Irshad, A. (Journal of Meat Science, 2015)
The aim of this study was to evaluate the effect of incorporation of potato (Solanum tuberosum) on the physico chemical and sensory quality of restructured spent hen meat blocks. Three levels of potato (boiled and mashed) viz. 8%, 12% and 16% were incorporated by replacing the lean meat in pre-standardized restructured spent hen meat blocks formulation. A significant increase (P
Keywords: Spent hen; Restructured meat blocks; Potato; Physico-chemical properties; Sensory attributes